Transparansi Dan Etika Keuangan Sebagai Pesan Dakwah: Refleksi Dari Kepemimpinan Usman Bin Affan RA - Hasanah, Uswatun; Nadhira, Ahmad (JURNAL SYIAR-SYIAR, 2025)
This study aims to reflect on the values of transparency and financial ethics in the leadership of Usman bin Affan RA and examine how these values can be communicated as da'wah messages in contemporary Islam. Employing a library research method with a descriptive qualitative approach, this study explores Islamic historical sources, Islamic finance literature, and da'wah communication theories to build a holistic understanding. The findings reveal that Usman bin Affan RA demonstrated financial practices grounded in transparency, accountability, and social justice, as seen in his management of personal and public wealth. These values align with the principles of modern Islamic finance and can be promoted as part of an applicable da'wah bil hal strategy. Furthermore, the study finds that communicating financial ethics can be carried out through educational approaches, digital technologies such as blockchain, the strengthening of Islamic financial institutions, and community engagement in social programs like zakat and waqf. In conclusion, the leadership of Usman bin Affan RA serves not only as a historical example but also as a strategic model for financial ethics da'wah to address the socio-economic challenges of today’s Muslim society.